Psychospiritual development and the formation of students’ religious motivation in islamic boarding schools: A literature review and conceptual model - Inayah Inayah; Widodo Winarso; Muslihudin (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
This study examines the psychospiritual development of students in Islamic boarding schools (pesantren), focusing on how religious habituation, internalization of spiritual values, and social dynamics influence students' psychological well-being and religious motivation. The literature review synthesizes findings from previous studies on the role of religious practices such as congregational prayers, Qur’an recitation, and dhikr in shaping students' spiritual awareness and identity. Psychospiritual development in pesantren is shown to be an integrative process, affecting both spiritual and psychological dimensions, including concentration, self-regulation, and emotional stability. The study also explores the role of social factors, such as peer attachment and social support, in reinforcing religiosity and promoting psychological resilience. Additionally, it highlights the importance of religiosity in fostering hope, life satisfaction, and resilience, which contribute to students' subjective well-being. This paper proposes a conceptual model of psychospiritual development in pesantren, illustrating the interaction between religious habituation, value internalization, psychological regulation, and social support. The study concludes that psychospiritual development is a gradual and transformative process that evolves from external ritual compliance to intrinsic religious motivation, contributing to a sustainable form of religious consciousness among students.